2017
DOI: 10.3329/bjz.v44i2.32766
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination in water and fishes from the Shitalakhya river at Narayanganj, Bangladesh

Abstract: River pollution has been a major problem in Bangladesh as industrial growth has led to increase which use lot of chemicals as raw materials. Moreover, anthropogenic activities continuously increase the amount of heavy metals in the water bodies especially in the lakes, canals, rivers and in aquatic organisms which is an alarming rate and has become an worldwide problem (Malik et al. 2010). Aquatic organisms such as fish and shell fish accumulate metals to concentrations many times higher than present in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The pH values were generally found to be constant due to the strong buffering capacity of water [30]. Similar ranges of pH were obtained by other researchers on Shitalakhya River [31,32]. The obtained result showed that pH values were within the EQS (6.5 to 8.5) range for inland surface water.…”
Section: Resultssupporting
confidence: 80%
“…The pH values were generally found to be constant due to the strong buffering capacity of water [30]. Similar ranges of pH were obtained by other researchers on Shitalakhya River [31,32]. The obtained result showed that pH values were within the EQS (6.5 to 8.5) range for inland surface water.…”
Section: Resultssupporting
confidence: 80%
“…As it is connected with the upper polluted river, it receives heavy loads of pollutants each year through this connecting rivers. Higher concentrations of Cu, Ni, Cr, As and Fe (figure S8) was found during dry season in Sitalakhya River water which were higher than DoE recommended standard concentrations for surface water (Tables 1 and 2) [12,37,106,109,110,111,112]. Heavy metal concentrations in sediment was found above US EPA safe limit (Table 3) [113].…”
Section: Sitalakhya River Pollutionmentioning
confidence: 99%